Шлюбний вибір та шлюбний договір як гендерна соціалізація молоді у звичаєвому праві - Малютіна, І. (Народна творчість та етнографія, 2007)
An ordinary rite, on the whole as well as official, aspired to strengthening and harmonious development of marriage/domestic relationship. Resulted examples show that marriage and salvage of marriage had a great value in the past.